Shell-imitated mechanically-enhanced photonic crystal paper, preparation method thereof and application of shell-imitated mechanically-enhanced photonic crystal paper in repeatable printing
By using a combination of imitation shell brick mud structure and zirconium phosphate layered material in photonic crystal paper, the scraping method is used to induce self-assembly and alternate arrangement, the problems of low mechanical strength and complicated preparation methods of photonic crystal paper are solved, and high strength is achieved , flexible and flame retardant photonic crystal paper, suitable for inkjet printing and safe storage.
Patent Information
- Application Number
- CN202411690502.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing photonic crystal paper has low mechanical strength and complicated and time-consuming preparation methods, making it difficult to adapt to ordinary inkjet printers, and there are security storage problems.
The brick mud structure that imitates shells and the zirconium phosphate layered material are combined, and self-assembly alternating arrangement is induced by scraping coating method to prepare photonic crystal paper with high tensile strength, high flexibility and flame retardant properties.
Photonic crystal paper that achieves high strength, flexibility and flame retardant properties can be adapted to commercially available inkjet printers, and has the functions of repeatable writing and printing, and has good security and storage.
Smart Images

Figure CN119490625A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rewritable photonic crystal paper materials, and specifically relates to a shell-like mechanically reinforced photonic crystal paper, a preparation method thereof, and a re-printable application thereof. Background Art
[0002] The invention of paper has greatly promoted the development of human civilization. However, most printed materials can only be used once and then discarded, resulting in a large amount of resource waste and environmental pollution. In order to overcome these problems, rewritable paper based on responsive photonic crystal materials has attracted widespread attention from researchers.
[0003] Photonic crystal materials are composed of materials with different dielectric constants arranged in an orderly periodic manner. The material can reflect light of a specific wavelength to produce structural colors. Photonic crystal paper containing a responsive gel component can be written using an aqueous solution as ink, and the writing part causes a reversible change in the lattice constant or refractive index, thereby producing two states of contrasting colors, achieving the purpose of rewritability. This type of photonic crystal paper has great potential to be compatible with commercially available inkjet printers and writing tools, and therefore shows great commercial prospects and is developing rapidly.
[0004] So far, related work has mainly focused on resolution, self-support, large-area manufacturing, multi-color writing and rewritability. However, due to the lack of structural and composition design, the mechanical properties of gel-based photonic crystal paper, such as strength, flexibility and stiffness, are difficult to match those of traditional commercial paper and cannot be adapted to ordinary inkjet printers. On the other hand, due to the low-throughput manufacturing and time-consuming assembly process of the assembly unit of photonic crystal materials, gel-based photonic crystal paper is difficult to manufacture continuously. In addition, due to the flammability of polymers, gel-based photonic crystal paper faces the problem of safe storage. Therefore, it is particularly important to find a commercially produced photonic crystal assembly unit and design an efficient and continuous preparation method to produce flame-retardant photonic crystal paper with a high strength-toughness-stiffness combination for commercial promotion. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the low mechanical strength and complicated and time-consuming preparation methods of existing photonic crystal paper, and provide a mechanically reinforced photonic crystal paper imitating shells, its preparation method and repeatable printing application. The photonic crystal paper of the present invention utilizes the swelling mechanism of the gel matrix to change the lattice spacing of the writing part, so that repeated writing and printing can be performed. This photonic crystal paper has a shell-like brick mud structure and a strong hydrogen bond between the zirconium phosphate layered material and the soft gel, so it has high tensile strength, high flexibility, high modulus and self-support. Since the selected zirconium phosphate has good thermal stability, and the brick mud structure reduces the oxygen permeability, the photonic crystal paper has flame retardant properties. Since the scraping method adopted is simple and fast, the photonic crystal paper can achieve continuous production. The photonic crystal paper is combined with water-based ink to achieve repeatable writing and printing, and has the advantages of durable color, economic and environmental protection, full-color writing, high-resolution printing and strong rewritability.
[0006] Based on the above purpose, the present invention adopts the following technical solutions: The present invention provides a method for preparing a shell-like mechanically reinforced photonic crystal paper, wherein the photonic crystal paper is obtained by alternatingly arranging zirconium phosphate layered materials and soft gels through shear force-induced self-assembly by scraping. The specific steps are as follows: (1) dispersing zirconium phosphate (α-ZrP), a non-volatile solvent, a monomer, a photoinitiator and a cross-linking agent in water to obtain a prepolymer solution of photonic crystal paper; (2) Drop a certain amount of prepolymer liquid of photonic crystal paper on the substrate, and use an adjustable film applicator to scrape the prepolymer liquid at a uniform speed to scrape the prepolymer liquid into a liquid film of a certain thickness. The shear force during the scraping process will induce the zirconium phosphate to be arranged in an orderly manner in the prepolymer liquid, thus obtaining a photonic crystal liquid film with obvious structural color; (3) The photonic crystal liquid film obtained in the above step (2) is peeled off from the substrate after being cured by ultraviolet polymerization to obtain photonic crystal paper.
[0007] Preferably, in step (1), based on the total mass of the prepolymer liquid as 100%, the mass ratios of the substances in the prepolymer liquid are: zirconium phosphate 45% to 60%, monomer 11% to 30%, non-volatile solvent 6.7% to 16%, cross-linking agent 0% to 1.15%, photoinitiator 0.001% to 0.1%, and the balance water.
[0008] Photonic crystal paper with different colors can be obtained by changing the content of non-volatile solvent or zirconium phosphate. The mechanical strength can be adjusted by changing the ratio of monomer, non-volatile solvent and cross-linking agent.
[0009] Preferably, in step (1), the diameter of the zirconium phosphate is 1-3 micrometers, the thickness is 10-100 nanometers, and the particle size dispersion index is not greater than 0.4. The particle size dispersion of the zirconium phosphate is reduced by gravity fractionation to obtain a zirconium phosphate with a particle size dispersion index not greater than 0.4.
[0010] Preferably, in step (1), the monomers in the prepolymer solution are composed of monomer 1 and monomer 2, wherein monomer 1 is diacetone acrylamide, accounting for 20-80% of the total weight of the monomers; monomer 2 is acrylamide, N-hydroxymethyl acrylamide, methacrylamide, N,N-dimethyl acrylamide and 4-acryloylmorpholine, or a mixture of two or more thereof in any proportion; the non-volatile solvent is polyethylene glycol 200, polyethylene glycol 400 and glycerol, or a mixture of two or more thereof in any proportion; the cross-linking agent is adipic acid dihydrazide, N,N'-methylenebisacrylamide and polyethylene glycol diacrylate; and the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone and ethyl 2,4,6-trimethylbenzoylphenylphosphonate, or a mixture of two or more thereof in any proportion.
[0011] Preferably, in step (2), the substrate is polyurethane or a glass sheet.
[0012] Preferably, in step (3), the UV polymerization curing is achieved by irradiating with UV light having a wavelength of 350-400 nm and a power of 30-40 W for 60 seconds to 5 minutes.
[0013] Furthermore, the continuous production of photonic crystal paper can be carried out on a continuous production device composed of a film scraper, a syringe pump, a syringe, a conveyor belt, an ultraviolet lamp, and a roll collection device.
[0014] Preferably, in continuous production, the prepolymer liquid is placed in a syringe, and a syringe pump is used to push the prepolymer liquid in the syringe at a uniform speed, so that the prepolymer liquid is squeezed out and dripped onto the polyurethane substrate, and then immediately scraped by a film scraper at a uniform speed to form a liquid film of a certain thickness. The conveyor belt conveys the liquid film to an ultraviolet lamp and irradiates it for 30s to 100s to complete the polymerization reaction, and the polymerized photonic crystal paper is collected into a roll by a roll collection device.
[0015] The shell-like mechanically reinforced photonic crystal paper prepared by the preparation method.
[0016] The above-mentioned shell-like mechanically reinforced photonic crystal paper is used as reusable printing paper or reusable writing paper.
[0017] The specific process is as follows: (1) Using an aqueous solution containing hygroscopic substances of different mass fractions as ink to write on the photonic crystal paper or adding the ink into an ink cartridge, and using a commercially available inkjet printer to perform inkjet printing on the photonic crystal paper; (2) Soak the written or printed photonic crystal paper in a 20-30% by mass polyethylene glycol 200 aqueous solution for 50-200 seconds, take it out and dry it to wash away the writing or printing traces; (3) Repeat steps (1) and (2).
[0018] Preferably, the hygroscopic substance in the ink is a hygroscopic salt such as lithium chloride, calcium chloride, magnesium chloride, zinc chloride, sodium nitrate, potassium acetate, polyethylene glycol 200, polyethylene glycol 400, glycerol and glucose, or a mixture of any two or more thereof. The residence time of the ink trace on the photonic crystal paper is 3 to 7 days.
[0019] The present invention combines photonic crystals with a unique brick-and-mortar structure to prepare mechanically reinforced, repeatedly printable, flame-retardant and continuously producible photonic crystal paper.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention prepares a photonic crystal paper with a shell brick mud structure, which has high tensile strength, high flexibility, high modulus and self-supporting properties and can be printed by a commercially available inkjet printer; (2) The zirconium phosphate layered material used in the present invention can be produced commercially, and the scraping method of the photonic crystal paper shortens the preparation cycle, and has the value of continuous production and practical use; (3) The zirconium phosphate selected in the present invention has good thermal stability, and the brick-and-mortar structure reduces the oxygen permeability, so that the photonic crystal paper has excellent flame retardant properties and high safe storage characteristics.
[0021] (4) The photonic crystal paper prepared by the present invention can use an aqueous solution containing a hygroscopic solute as ink, and can be used to write or print words or patterns of various sizes, precisions and colors through a brush, a dip pen, an ink-filled marker or a commercially available inkjet printer. The handwriting and printed patterns can be maintained for at least one week, and can be quickly erased by a polyethylene glycol aqueous solution, and can be reprinted up to hundreds of times.
[0022] (5) The strategy of using layered materials to prepare shell-like photonic crystal paper in the present invention can provide new ideas for other researchers to manufacture photonic crystal materials with high mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the cross section of the mechanically enhanced photonic crystal paper prepared in Example 1 of the present invention.
[0024] Figure 2 This is the stress-strain curve of the mechanically enhanced photonic crystal paper prepared in Example 1 of the present invention.
[0025] Figure 3 This is a flame retardant test of the mechanically reinforced photonic crystal paper prepared in Example 1 of the present invention.
[0026] Figure 4 The text is written in different colors on the photonic crystal paper using calcium chloride aqueous solution with different concentrations.
[0027] Figure 5 A photograph was printed one hundred times on photonic crystal paper using a commercial inkjet printer equipped with an aqueous solution of calcium chloride. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific implementation methods. The raw materials in the examples are all commercially available. Unless otherwise specified, the reagents, methods and equipment used in the present invention are all conventional reagents, methods and equipment in the technical field. The present invention described herein is only used to explain the present invention and is not intended to limit the present invention.
[0029] Example 1 A method for preparing a shell-like mechanically reinforced photonic crystal paper, wherein the photonic crystal paper is obtained by alternating the arrangement of zirconium phosphate layered materials and soft gel through shear force induced self-assembly by scraping. The specific steps are as follows: (1) Disperse 10 g of zirconium phosphate layered material (α-ZrP, diameter of 1-3 μm, thickness of about 50 nm) in 40 mL of water, let stand for 48 h for gravity distillation, take the upper layer solution and centrifuge and dry to obtain zirconium phosphate with a particle size dispersion index (PDI) of 0.34. Based on the total mass of the prepolymer solution as 100%, the mass fractions of the substances in the prepolymer solution are as follows: 50% zirconium phosphate, 8.99% polyethylene glycol 200, 8.99% diacetone acrylamide, 17.97% acrylamide, 0-1.15% (specifically 0, 0.15%, 0.29%, 0.58%, 1.15%) adipic acid dihydrazide (ADH), 0.09 wt% 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the remainder is water. Mix the substances evenly to obtain a prepolymer solution for photonic crystal paper.
[0030] (2) Drop 2 g of photonic crystal paper prepolymer onto a glass plate and use an adjustable film applicator to scrape the prepolymer at a constant speed to form a liquid film with a thickness of 350 μm at a speed of 6 cm / s. The shear force during the film scraping process will induce the zirconium phosphate to be arranged in an orderly manner in the prepolymer, thus obtaining a photonic crystal liquid film with obvious structural color.
[0031] (3) The photonic crystal liquid film obtained in the above step (2) was irradiated under ultraviolet light (wavelength 365 nm, power 36 W) for 60 seconds for polymerization, and then peeled off from the glass plate to obtain blue photonic crystal paper. Figure 1 The SEM image shows the shell brick-like structure of the prepared photonic crystal paper.
[0032] (4) Figure 2 The adjustable mechanical properties of the photonic crystal paper are shown. As the mass fraction of adipic acid dihydrazide increases from 0 to 1.15%, the tensile strength of the photonic crystal paper is approximately 11.6 MPa, 15.6 MPa, 17.8 MPa, 20.3 MPa and 24.2 MPa, respectively, the toughness is approximately 13.1 MJ / m³, 9.8 MJ / m³, 9.7 MJ / m³, 5.5 MJ / m³ and 4.2 MJ / m³, respectively, and the modulus is approximately 94.4 MPa, 152.4 MPa, 225.9 MPa, 317.6 MPa and 501.1 MPa, respectively. The tensile strength of the photonic crystal paper is that of pure polydiacetone acrylamide- co - polyacrylamide gel matrix (i.e., zirconium phosphate is omitted in step (1), and the rest is the same as the gel matrix obtained in steps (1) to (3)). After being ignited by an open flame for 10 seconds and then the fire source is removed, the prepared photonic crystal paper extinguishes itself within 1 second and has flame retardancy. Figure 3 .
[0033] Example 2 A method for preparing a shell-like mechanically reinforced photonic crystal paper, wherein the photonic crystal paper is obtained by alternating the arrangement of zirconium phosphate layered materials and soft gel through shear force induced self-assembly by scraping. The specific steps are as follows: (1) Disperse 10 g of zirconium phosphate layered material (α-ZrP, diameter of 1-3 μm, thickness of about 50 nm) in 40 mL of water, let stand for 48 h for gravity distillation, and centrifuge and dry the upper layer solution to obtain zirconium phosphate with a particle size dispersion index (PDI) of 0.34. Based on the total mass of the prepolymer solution as 100%, the mass fractions of the substances in the prepolymer solution are as follows: 50% zirconium phosphate, 6.73%-15.7% glycerol (specifically 6.73%, 8.97%, 11.21%, 13.46%, 15.70%), 17.97% diacetone acrylamide, 8.99% 4-acryloylmorpholine, 0.58% N,N'-methylenebisacrylamide, 0.09% ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and the remainder is water. Mix the substances evenly to obtain a prepolymer solution for photonic crystal paper.
[0034] (2) Drop 2 g of photonic crystal paper prepolymer onto a glass plate and use an adjustable film applicator to scrape the prepolymer at a constant speed to form a liquid film with a thickness of 350 μm at a speed of 6 cm / s. The shear force during the film scraping process will induce the zirconium phosphate to be arranged in an orderly manner in the prepolymer, thus obtaining a photonic crystal liquid film with obvious structural color.
[0035] (3) The photonic crystal liquid film obtained in the above step (2) was irradiated under ultraviolet light (wavelength of 365 nm, power of 36 W) for 60 seconds for polymerization, and then peeled off from the substrate to obtain blue, cyan, green, yellow and red photonic crystal papers; (4) As the glycerol content decreases from 15.7% to 6.73%, the tensile strength of the photonic paper is 12.4MPa, 14.3MPa, 18.9MPa, 21.6MPa and 25.1MPa, the toughness is 4.1MJ / m³, 3.5MJ / m³, 2.7MJ / m³, 1.9MJ / m³ and 1.4MJ / m³, and the modulus is 15.4MPa, 30.3MPa, 535.1MPa, 826.3MPa and 1271.9MPa. The tensile strength of the photonic crystal paper is higher than that of pure polydiacetone acrylamide- co -200 to 300 times of the polyacrylamide gel matrix (i.e., the zirconium phosphate is omitted in step (1), and the other steps are the same as those obtained in steps (1) to (3)). After being ignited by an open flame for 10 seconds and then the fire source is removed, the prepared photonic crystal paper extinguishes itself within 1 second, and has flame retardancy.
[0036] Example 3 A method for preparing a shell-like mechanically reinforced photonic crystal paper, wherein the photonic crystal paper is obtained by alternating the arrangement of zirconium phosphate layered materials and soft gel through shear force induced self-assembly by scraping. The specific steps are as follows: (1) Disperse 10 g of zirconium phosphate layered material (α-ZrP, diameter of 1-3 μm, thickness of about 50 nm) in 40 mL of water, let stand for 48 h for gravity fractionation, and centrifuge and dry the upper layer solution to obtain zirconium phosphate with a particle size dispersion index (PDI) of 0.34. Based on the total mass of the prepolymer solution as 100%, the mass fractions of the substances in the prepolymer solution are as follows: 45%-60% zirconium phosphate (specifically 45%, 50%, 55%, 60%), 8.99% polyethylene glycol 200, 17.97% diacetone acrylamide, 8.99% acrylamide, 0.58% N,N'-methylenebisacrylamide, 0.09% 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, and the remainder is water. Mix the substances evenly to obtain a prepolymer solution for photonic crystal paper.
[0037] (2) Drop 2 g of photonic crystal paper prepolymer onto a glass plate and use an adjustable film applicator to scrape the prepolymer at a constant speed to form a liquid film with a thickness of 350 μm at a speed of 6 cm / s. The shear force during the film scraping process will induce the zirconium phosphate to be arranged in an orderly manner in the prepolymer, thus obtaining a photonic crystal liquid film with obvious structural color.
[0038] (3) The photonic crystal liquid film obtained in the above step (2) was irradiated under ultraviolet light (wavelength of 365 nm, power of 36 W) for 60 seconds for polymerization, and then peeled off from the substrate to obtain yellow, green, cyan and blue photonic crystal papers; (4) As the zirconium phosphate content increases from 45% to 60%, the tensile strength of the photonic paper is 17.3MPa, 19.6MPa, 23.2MPa and 25.6MPa, the toughness is 6.3 MJ / m³, 5.8 MJ / m³, 5.1 MJ / m³ and 4.8 MJ / m³, and the modulus is 280.1MPa, 300.5MPa, 366.8MPa and 420.6MPa. The tensile strength of the photonic crystal paper is higher than that of pure polydiacetone acrylamide- co -200 to 300 times of the polyacrylamide gel matrix (i.e., the zirconium phosphate is omitted in step (1), and the other steps are the same as those obtained in steps (1) to (3)). After being ignited by an open flame for 10 seconds and then the fire source is removed, the prepared photonic crystal paper extinguishes itself within 1 second, and has flame retardancy.
[0039] Example 4 Mechanically enhanced photonic crystal paper with multi-color writing and reproducible printing properties: (1) Calcium chloride with a mass fraction of 15%-30% was dissolved in water as ink, and then a marker pen filled with ink of different calcium chloride concentrations was used to write on the blue photonic crystal paper with a mass fraction of adipic acid dihydrazide of 0.58% in Example 1. As the concentration of calcium chloride increased, the gel swelling degree of the writing area gradually increased, and the color red shift of the photonic crystal paper increased, and finally a font ranging from cyan to orange was written, achieving multi-color writing, as shown in FIG. Figure 4 , where the calcium chloride concentrations from top to bottom are 15%, 20%, 25% and 30%.
[0040] (2) The 20 wt % calcium chloride ink prepared in step (1) was poured into an empty ink cartridge of a commercially available HP inkjet printer, and then the blue photonic crystal paper having a mass fraction of adipic acid dihydrazide of 0.58% in Example 1 was inkjet printed to obtain clear fonts or patterns.
[0041] (3) Soak the photonic crystal paper printed with information in step (2) in a 25% by mass polyethylene glycol 200 aqueous solution for 90 seconds, then take it out and dry it at 60°C for 2 minutes. As the salt ink is washed out, the printed information will disappear, thus erasing the information. Then the erased photonic crystal paper can be inkjet printed again. This "print-erase-print" process can be repeated hundreds of times. For details, see Figure 5 .
[0042] Example 5 Demonstration of continuous production of mechanically enhanced photonic crystal paper: (1) Disperse 1000g of zirconium phosphate layered material (α-ZrP, diameter of 1-3 microns, thickness of about 50 nanometers) in 4000mL of water, let it stand for 48 hours for gravity distillation, and centrifuge and dry the upper layer solution to obtain zirconium phosphate with a particle size dispersion index (PDI) of 0.34. Based on the total mass of the prepolymer solution as 100%, the mass fractions of the substances in the prepolymer solution are as follows: 50% zirconium phosphate, 8.99% polyethylene glycol 200, 8.99% diacetone acrylamide, 17.97% acrylamide, 0.58% adipic acid dihydrazide, 0.09% 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the remainder is water. Mix the substances evenly to obtain a prepolymer solution for photonic crystal paper.
[0043] (2) A film scraper, a syringe pump, a syringe, a conveyor belt, a UV lamp, and a roll collection device are assembled into a micro-continuous production device to demonstrate the continuous production of photonic crystal paper.
[0044] (3) Pour 100g of prepolymer liquid of photonic crystal paper into a syringe, and use a syringe pump to push the syringe at a constant speed to squeeze out the prepolymer liquid and drip it onto the polyurethane substrate. At the same time, the conveyor belt drives the polyurethane at a speed of 1cm / s, and produces relative motion with the scraper of the film applicator. The shear force generated will induce the zirconium phosphate to be arranged in an orderly manner in the prepolymer liquid, that is, a continuous photonic crystal liquid film with obvious structural color is obtained. Continuously irradiate under the ultraviolet lamp above the conveyor belt for light curing, and the polymerized photonic crystal paper is collected into a roll by a roll collection device at the end of the conveyor belt.
[0045] The above description is only an embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any simple modification, equivalent change and improvement made to the above embodiment by any technician familiar with the profession without departing from the technical solution of the present invention and based on the technical essence of the present invention shall still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a shell-like mechanically reinforced photonic crystal paper, characterized in that: The specific steps are as follows: (1) dispersing zirconium phosphate, a non-volatile solvent, a monomer, a photoinitiator and a cross-linking agent in water to obtain a prepolymer solution of photonic crystal paper; (2) applying the prepolymerized liquid of the photonic crystal paper onto the substrate by scraping to obtain a photonic crystal liquid film; (3) The photonic crystal liquid film obtained in the above step (2) is peeled off from the substrate after being cured by ultraviolet polymerization to obtain photonic crystal paper.
2. The preparation method according to claim 1, characterized in that: In step (1), taking the total mass of the prepolymer liquid as 100%, the mass ratios of the substances in the prepolymer liquid are: zirconium phosphate 45% to 60%, monomer 11% to 30%, non-volatile solvent 6.7% to 16%, cross-linking agent 0% to 1.15%, photoinitiator 0.001% to 0.1%, and the balance water.
3. The preparation method according to claim 1, characterized in that: In step (1), the diameter of the zirconium phosphate is 1-3 microns, the thickness is 10-100 nanometers, and the particle size dispersion index is not greater than 0.
4.
4. The preparation method according to claim 1, characterized in that: In step (1), the monomers in the prepolymer solution are composed of monomer one and monomer two, wherein monomer one is diacetone acrylamide, accounting for 20-80% of the total weight of the monomers; monomer two is acrylamide, N-hydroxymethyl acrylamide, methacrylamide, N,N-dimethyl acrylamide and 4-acryloylmorpholine, or a mixture of two or more thereof in any proportion; the non-volatile solvent is polyethylene glycol 200, polyethylene glycol 400 and glycerol, or a mixture of two or more thereof in any proportion; the cross-linking agent is one of adipic acid dihydrazide, N,N'-methylenebisacrylamide and polyethylene glycol diacrylate; and the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone and ethyl 2,4,6-trimethylbenzoylphenylphosphonate, or a mixture of two or more thereof in any proportion.
5. The preparation method according to claim 1, characterized in that: In step (2), the substrate is polyurethane or a glass sheet.
6. The preparation method according to claim 1, characterized in that: In step (3), during the UV polymerization curing, UV light with a wavelength of 350-400 nm and a power of 30-40 W is used for 60 seconds to 5 minutes.
7. Shell-like mechanically reinforced photonic crystal paper prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the shell-like mechanically reinforced photonic crystal paper according to claim 7 as reusable printing paper or reusable writing paper.
9. The use according to claim 8, characterized in that: The process is as follows: (1) Using an aqueous solution containing hygroscopic substances of different mass fractions as ink to write on the photonic crystal paper or adding the ink into an ink cartridge, and using a commercially available inkjet printer to perform inkjet printing on the photonic crystal paper; (2) Soak the written or printed photonic crystal paper in a 20-30% by mass polyethylene glycol 200 aqueous solution for 50-200 seconds, take it out and dry it to wash away the writing or printing traces; (3) Repeat steps (1) and (2).
10. The use according to claim 9, characterized in that: In step (1), the hygroscopic substance in the ink is one or a mixture of any proportion of two or more of lithium chloride, calcium chloride, magnesium chloride, zinc chloride, sodium nitrate, potassium acetate, polyethylene glycol 200, polyethylene glycol 400, glycerol and glucose.
Citation Information
Patent Citations
Photonic crystal paper and preparation method thereof
CN102304263A
Gradient humidity-sensitive photonic crystal paper, preparation method and application of gradient humidity-sensitive photonic crystal paper in anti-counterfeiting writing or anti-counterfeiting printing
CN117467091A
A nanocomposite and a method for producing a nanocomposite
EP2752466A2
Cited By
Microphase separation photonic crystal gel and preparation method, structural color regulation method and application thereof
CN119735765A
Microphase-separated photonic crystal gel, its preparation method, structural color regulation method and application
CN119735765B